An integrated approach to assessing the ecological state of urban park soils, Kirov, Russia - S. G. Skugoreva; L. I. Domracheva; A. I. Fokina; T. I. Kutyavina; O. M. Abdukhalilov; V. N. Kulakov; T. Ya. Ashikhmina (Юг России: экология, развитие, 2023)
Aim. Assess the ecological state of soils in park areas and public gardens in the city of Kirov, Kirov region, Russia, which are located near areas of heavy traffic, using an integrated approach based on data from physicochemical, microbiological analyzes and biotesting.Material and Methods. Soil samples were taken at various sites in the 60th Anniversary of the USSR Square, in the S.M. Kirov Park and in the 50th Anniversary of the Komsomol Park. The concentration of inorganic ions and the content of polycyclic aromatic hydrocarbons (PAHs) in the soils were determined by ionic and high‐performance liquid chromatography, respectively. The total content of heavy metals (HM)was determined by atomic absorption spectroscopy. Quantitative registration of microorganisms was carried out by the method of limiting dilutions with subsequent inoculation on selective nutrient media. Biotesting was carried out using the protozoa Paramecium caudatum and the Ecolum bacterial test system.Results. The features of the ionic composition of soils in Kirov parks were studied. In the aqueous extract of the studied soils, sulphate and chloride ions predominated among anions, and calcium ions among cations. Among the groups of microorganisms studied, ammonifying bacteria take the leading positions, the share of which in the microbial complex reaches 65.35–86.54%. There is a close relationship between the content of nutrients and the number of ammonifiers. The gross concentration of HMs in soil samples from parks in Kirov did not exceed their approximate permissible concentration, while the content of Pb, Zn, and Cо was up to 3.1 times higher than the regional background. The highest content of PAHs, maximum values of total carcinogenic activity and toxicity to P. caudatum were found in soil samples taken from areas near highways. Conclusion. The ecological state of urban park soils in Kirov in general can be characterised as satisfactory. Nevertheless, for park soils in the immediate vicinity of highways, increased values of PAH concentration were revealed. Determination of the PAH content in soils can be recommended for inclusion in the environmental monitoring programme in cities because of the persistence of PAHs in the environment, their mutagenic and carcinogenic properties, and the lack of standards for the content of most PAHs in natural environments.